Maintained gait in persons with arthrogryposis from childhood to adulthood - Åsa Bartonek; Mikael Reimeringer; Marie Eriksson (BMC Musculoskeletal Disorders)
Abstract Background Individuals with arthrogryposis multiplex congenita (AMC) exhibit a range of modes of ambulation, from walking independently to requiring a wheelchair. Presence of joint contractures and muscle strength plays a crucial role, and, in some patients, orthoses are necessary to facilitate or enable walking. Methods Gait was assessed with a three-dimensional (3D) gait analysis, calculated as a gait deviation index (GDI) of nine kinematic variables, and compared between childhood and adulthood. Results A total of 12 persons, 8 with community and 4 with household ambulation, who had undergone a 3D gait analysis in childhood (CH) and as an adult (follow-up, FU) at the same gait laboratory were enrolled in the study. At the FU, three, five, and four participants respectively were categorized based on need of joint stabilization while walking as AMC1 using knee-ankle-orthoses (KAFOs) with locked knee joints, AMC2 using KAFOs with free-articulating knee joint or ankle–foot-orthoses (AFOs) and AMC3 using insoles or shoes. Two participants in AMC2 had changed from AFOs to insoles or shoes between CH and FU. There were no differences in joint contractures between the AMC groups at CH or FU. Two participants had orthopaedic surgery between CH and FU. The GDI of the leg with the lowest GDI score at CH vs FU was median [min, max] 55.67 [41.79, 65.14] vs 48.4 [42.67, 56.30] (p = 1.000) in AMC1, 81.25 [59.42, 84.12] vs 68.96 [47.68, 70.33] (p = 0.043) in AMC2, and 73.15 [43.94, 91.72] vs 73.46 [50.82, 75.24] (p = 1.000) in AMC3. Time and distance parameters of cadence, walking speed, step length, and step width did not differ between the CH and FU, nor were there differences in satisfaction with the device or the service at the FU. Conclusion A difference in the GDI was found in one of the AMC groups between childhood and adulthood that could not be explained by factors such as contractures or muscle strength. This study reflects that gait is maintained in ambulating persons with AMC who were offered an orthosis program that has been available from childhood into adulthood.